KONSEP PARADIGMA ILMU-ILMU SOSIAL DAN RELEVANSINYA BAGI PERKEMBANGAN PENGETAHUAN - Happy Susanto (MUADDIB Jurnal Kependidikan dan Keislaman, 2014)
The main purpose of this study is to explain the various concepts of paradigms in the social sciences. There are three paradigms in the social sciences, the paradigm of social facts, social definition, and social behavior. Social fact is something that is beyond the individual reality therefore social fact divided into two terms of the material entity and non material entity. Material entity is something tangible goods, while the unity of the non material entity is considered to be something that no goods. Social definition paradigm directs attention to how to interpret human social life or how they form a real social life. While the paradigm of social behavior discussing on individual behavior that takes place in an environment that causes or changes due to subsequent behavior. The differences between paradigm must be seen as positive because each paradigms can support buliding scientific tradition